Расчет параметров автоколебаний давления рабочей жидкости в гидросистеме стабилизатора канала вертикального наведения танковой пушки - Александрова, Татьяна Евгеньевна; Александрова, И. Е.; Лазаренко, А. А. (НТУ "ХПИ", 2011)
The problem of finding the amplitudes and frequencies of oscillations of pressure fluid in the hydraulic system stabilizer channel vertical guidance tank gun and measured their impact on the accuracy of stabilization.
Keywords: танковая пушка; стабилизатор; вертикальное наведение; гидроцилиндр